Penguatan Pemahaman Siswa Tentang Biodiversitas di Indonesia Melalui Discovery learning dan Pengenalan Maskot Flora dan Fauna Daerah : (Strengthening Students' Understanding of Biodiversity in Indonesia through Discovery learning and Introduction of Regional Flora and Fauna Mascots) - Sembiring, Al Khudri; Ramadansur, Rahmat; Akbar, Muhammad Azhari (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The approach to biology learning methods with biodiversity material that explores natural potential such as recognizing regional flora and fauna mascots can be an idea to form positive student characters, one of which is caring for the environment and having pride in regional identity. This study aims to analyze the feasibility and effectiveness of the module as an enrichment of biodiversity material based on local potential through the introduction of regional flora and fauna mascots on the learning outcomes of students of SMAN 1 Sungai Apit and students' responses to the module. This research was conducted in three stages, namely problem analysis, development, and testing with purposive sampling technique. The discovery learning model has fulfilled the scientific principles, but the design is not complete according to the syntax of the discovery learning model in the planning stage and the implementation stage. Evaluation, which is used by observing student activeness and conducting tests to students, namely by assignment and practice. In addition to student participation, it takes the active role of subject teachers and support facilities from the school. Abstrak. Pendekatan metode pembelajaran biologi dengan materi biodiversitas yang menggali potensi alam seperti mengenal maskot flora dan fauna daerah dapat menjadi sebuah gagasan untuk membentuk karakter positif siswa salah satunya peduli lingkungan dan memiliki kebanggaan atas identitas daerah. Studi ini mengeksplorasi kelayakan dan efektivitas modul yang bertujuan memperkaya pendidikan biodiversitas melalui pengenalan maskot flora dan fauna daerah. Studi ini dilakukan di SMAN 1 Sungai Apit dengan mengikuti tiga tahap: analisis masalah, pengembangan, dan pengujian. Studi ini menemukan bahwa meskipun model discovery learning sesuai dengan prinsip-prinsip ilmiah, perlu penyempurnaan lebih lanjut dalam desain dan implementasinya. Modul menunjukkan potensi dalam meningkatkan keterlibatan siswa dan kesadaran lingkungan, tetapi membutuhkan peran aktif guru dan fasilitas sekolah yang memadai untuk efektivitas optimal.